Implementasi Algoritma Hebb Rule Pada Diagnosa Penyakit Kolik Abdomen Pada Orang Dewasa - Etty Diana Manurung; Berto Nadeak; Eferoni Ndruru (STMIK Budi Darma, 2020)
In the current era of globalization, the development of computers in the health sector has become increasingly rapid. Computerized systems are needed especially in handling a disease. Because sometimes doctors, nurses find it difficult to know the type of illness suffered by adults, children and the elderly without a good computerized system. Abdominal colic, for example. Abdominal colic is a disease where there is an unpleasant feeling in the oral cavity between the thigh border and the chest rib border. This disease is caused by several factors, for example, eating is already full, eating a lot of acid, spicy and also drinking lots of alcohol. And usually occurs in adults. Where symptoms are symptoms such as nausea, vomiting and noisy intestines and excessive farts. With these symptoms, which becomes a control that a person has abdominal colic disease. Therefore the author made a study of the implementation of the HB rule on the diagnosis of abdominal colic disease. Theebb rule algorithm is a simple and uncomplicated learning method in the process, with the aim of minimizing the risk of disease problems that occur in patients, especially adults